Antissemitismo nos livros infantis na Alemanha Nazista (1939 - 1945) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This paper aims to analyze and understand the antisemitic images in children's books during the period of Nazi Germany (1933 - 1945). This work was based on a literature and image analysis. The images analyzed are loaded with hate and prejudice messages, and because of that this work uses the book written by Adolf Hitler, Mein Kampf, to make a contextual analysis and be able to explain, and deconstruct, its message in a direct way. Images can be an important source to be used in the classroom, but it is necessary to have a contextualization and knowledge about the theme and how to work with these images. As a final result there is the production of a didactic material instructing how the images produced by the Nazi government can be used in the classroom for a critical knowledge of the theme and for the deconstruction of the hatred produced and propagated by the images of Nazi Germany in children's books.
Keywords: Nazismo; Antissemitismo; Imagens; Representação; Ensino de História; Nazism; Antisemitism; Images; Representation; History Teaching; CNPQ::CIENCIAS HUMANAS::HISTORIA